Using the given function, it is found that:
a) She earns $36 after 26 years.
b) The original function was shifted 3 units to the right and 1 unit up.
Her profit in x years after 2015 is given by:
[tex]g(x) = 12\sqrt[3]{x + 1}[/tex]
Item a:
She earns $36 after x years, considering that g(x) = 36, hence:
[tex]g(x) = 12\sqrt[3]{x + 1}[/tex]
[tex]36 = 12\sqrt[3]{x + 1}[/tex]
[tex]\sqrt[3]{x + 1} = 3[/tex]
[tex](\sqrt[3]{x + 1})^3 = 3^3[/tex]
[tex]x + 1 = 27[/tex]
[tex]x = 26[/tex]
She earns $36 after 26 years.
Item b:
The new function is:
[tex]h(x) = 12\sqrt[3]{x - 2} + 1[/tex]
Which can be basically written as:
[tex]h(x) = f(x - 3) + 1[/tex]
Hence the original function was shifted 3 units to the right and 1 unit up.
More can be learned about functions at https://brainly.com/question/25537936